Death in contemporary Western culture - Woods, Timothy J. (Islam and Christian-Muslim relations, 2007)
As a Christian priest and minister, I have inevitably taken responsibility for getting to know a wide variety of families as they faced the dying or death of a relative, and in the majority of cases I have not previously known the family. Unlike many other occasions for pastoral contact, the encounter with death has meant that I have met families when they are ready to be very open and honest about their feelings. In this paper, beginning with reference to a contemporary film, I explore the question of the concept of death in Western culture today. I am particularly indebted to Grace Jantzen for shaping a key question: Is it necrophilia or necrophobia that best describes the attitude of Western culture to death? I shall examine these two particular lines of thinking prior to offering some reflections on ways in which the Christian tradition approaches the subject.